Dynamic Range Analysis of the Phase Generated Carrier Demodulation Technique. (17th March 2014) - Plotnikov, M. J.; Kulikov, A. V.; Strigalev, V. E.; Meshkovsky, I. K.
Abstract : The dependence of the dynamic range of the phase generated carrier (PGC) technique on low-pass filters passbands is investigated using a simulation model. A nonlinear character of this dependence, which could lead to dynamic range limitations or measurement uncertainty, is presented for the first time. A detailed theoretical analysis is provided to verify the simulation results and these results are consistent with performed calculations. The method for the calculation of low-pass filters passbands according to the required dynamic range upper limit is proposed.